WWP2 confers risk to osteoarthritis by affecting cartilage matrix deposition via hypoxia associated genes. Issue 1 (January 2023) - Tuerlings, M.; Janssen, G.M.C.; Boone, I.; van Hoolwerff, M.; Rodriguez Ruiz, A.; Houtman, E.; Suchiman, H.E.D.; van der Wal, R.J.P.; Nelissen, R.G.H.H.; Coutinho de Almeida, R.; van Veelen, P.A.; Ramos, Y.F.M.; et al.
Summary: Objective: To explore the co-expression network of the osteoarthritis (OA) risk gene WWP2 in articular cartilage and study cartilage characteristics when mimicking the effect of OA risk allele rs1052429-A on WWP2 expression in a human 3D in vitro model of cartilage. Method: Co-expression behavior of WWP2 with genes expressed in lesioned OA articular cartilage ( N = 35 samples) was explored. By applying lentiviral particle mediated WWP2 upregulation in 3D in vitro pellet cultures of human primary chondrocytes ( N = 8 donors) the effects of upregulation on cartilage matrix deposition was evaluated. Finally, we transfected primary chondrocytes with miR-140 mimics to evaluate whether miR-140 and WWP2 are involved in similar pathways. Results: Upon performing Spearman correlations in lesioned OA cartilage, 98 highly correlating genes (| ρ | > 0.7) were identified. Among these genes, we identified GJA1, GDF10, STC2, WDR1, and WNK4 . Subsequent upregulation of WWP2 on 3D chondrocyte pellet cultures resulted in a decreased expression of COL2A1 and ACAN and an increase in EPAS1 expression. Additionally, we observed a decreased expression of GDF10, STC2, and GJA1 . Proteomics analysis identified 42 proteins being differentially expressed with WWP2 upregulation, which were enriched for ubiquitin conjugating enzyme activity. Finally, upregulation of miR-140 in 2D chondrocytes resulted in significant upregulation of WWP2 and WDR1 . Conclusions: Mimicking the effect of OA risk allele rs1052429-A on WWP2 expression initiates detrimental processes in the cartilage shown by a response in hypoxia associated genes EPAS1, GDF10, and GJA1 and a decrease in anabolic markers, COL2A1 and ACAN .